Preclinical pharmacokinetics, distribution, metabolism and excretion of disitamab vedotin - Ling Wang; Limeng Zhu; Fengzhu Wang; Lihou Dong; Zhihao Liu; Fang Chen; Jing Jiang (ADMET and DMPK)
Background and purpose: Disitamab vedotin is an antibody-drug conjugate (ADC) composed of a humanized IgG1 monoclonal antibody (mAb) targeting HER2 conjugated to monomethyl auristatin E(MMAE) via a cleavable dipeptide linker. Experimental approach: The pharmacokinetics, distribution, catabolism/meta-bolism and elimination properties of disitamab vedotin and its payload MMAE were characterized in rats and tumour-bearing mice. Key results: The configured mAb and total antibody showed linear dynamic characteristics. Moreover, the molecular structure of disitamab vedotin effectively reduces the exposure of MMAE, which has a fast clearance. Two radiolabeled probes were developed to track the fate of different components of the disitamab vedotin, including 125I labelled antibody and 3H labelled MMAE payload of the ADC. Following a single intravenous administration of the radiolabeled probes to the tumour-bearing mice and rats, blood, various tissues, and excreta samples were collected and analyzed for radioactivity and to characterize the metabolites/catabolites. Disitamab vedotin and free MMAE (FM) were majorly distributed in tissues and organs with rich blood flow. Moreover, both disitamab vedotin and MMAE have higher and longer exposure in tumour tissue. Disitamab vedotin was mainly eliminated through renal excretion, while the FM was mainly eliminated through the biliary faecal route (>70 %) and a small fraction (<10 %) was eliminated through renal excretion in the form of catabolites/metabolites, among which, MMAE was identified as the major species, along with 10 other minor species. Conclusion: These studies provided significant insight into disitamab vedotin pharmacokinetics, distribution, metabolism and elimination properties, which supports the clinical development of disitamab vedotin.